Medicinal bioactive compounds to functional foods from geochemical signatures marine biomasses: sea cucumbers, macroalgae and crown of thorns biomasses - Ghazali, Farid Che; Edinur, Hisham Atan; K. N. S, Sirajudeen; B. Aroyehun, Abdul Qudus; Abdul Razak, Shariza (Life Sciences, Medicine and Biomedicine, 2019)
Recognition of health benefits associated with consumption of marine derived biomasses is one of the most promising developments in human nutrition and disease-prevention research. This endeavor for bioactives and functional ingredients discovery from marine sources is “experience driven,” as such the search for therapeutically useful synthetic drugs, and functional components is like “looking for a needle in a haystack,” thus a daunting task. Zoonotic infection, adulteration, global warming and religious belief can be the star-gate barrier: - For example, the outsourcing for Glycosaminoglycans (GAGs), a pharmacologically bioactive compound have emerged as novel biomarkers and molecular players both within tumor cells and their microenvironment, as they integrate signals from growth factors, chemokines, integrins, and cell-cell matrix adhesion. As such, worldwide initiatives in outsourcing from geochemical signatures marine biomasses are flourishing. Most of these scientific interests are related to marketable compounds optimised via biotechnology applications. Approximately 50% of the US FDA approved drugs during 1981–2002 consist of either marine metabolites or their synthetic analogs. These bioactive compounds acts as antioxidant, peptides, chitoligosaccharides derivatives, sulfated polysaccharides, phlorotannins and carotenoids. Highlights from works to harness and provide scientific support to folk medicine much claimed legacy, pertaining to geochemical signatures vouchered sea cucumbers, macroalgae and crown of thorns starfish will be extrapolated.